REACTIVE CHANGES IN THE VESSELS OF THE HEMOMICROCIRCULATORY BED IN THE LOBULES OF THE SUBMANDIBULAR SALIVARY GLANDS OF RATS UNDER THE INFLUENCE OF A COMPLEX OF FOOD ADDITIVES - Yeroshenko, G.A.; Shevchenko, K.V.; Bieliaiev, I.S.; Gryhorenko, A.S.; Sokolenko, V.M.; Onipko, V.V.; Peredera, R.V. (World of Medicine and Biology, 2025)
The study presents morphometric data on the effects of a combination of food additives on the condition of the hemomicrocirculatory vessels in the lobules of rat submandibular salivary glands. It was found that early exposure to monosodium glutamate, sodium nitrite, and Ponceau 4R leads to narrowing of the vessels in the resistive, exchange, and capacitive segments, resulting in tissue hypoxia. This directly impairs salivary gland function and may contribute to the development of dry mouth. As part of the body’s compensatory and restorative responses, dilation of the exchange segment vessels was observed, indicating intensified secretion and salivation processes. However, persistent spasms in arterioles and capillaries, along with dilation of venules, contribute to interstitial tissue edema, impaired oxygen and amino acid delivery to the terminal acinar cells, and ultimately to structural remodeling of the secretory apparatus in favor of carbohydrate over protein synthesis. This shift negatively affects saliva quality and reduces its enzymatic activity.